Negative pole piece, preparation method thereof and battery

By applying a fast charging coating in the overhang area of ​​the negative electrode sheet, the problem of lithium ions not being able to be quickly transmitted during fast charging is solved, the lithium extraction phenomenon is reduced, and the performance and safety of the battery are improved.

CN119852307APending Publication Date: 2025-04-18安徽得壹能源科技有限公司
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510042427.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

During the fast charging process of lithium-ion batteries, lithium ions cannot enter and exit the vertical direction of the graphite layer quickly, resulting in increased electrochemical polarization. Lithium is reduced to metal lithium on the surface of the negative electrode, and the dendritic structure pierces the separator, causing short circuits and safety accidents inside the battery. At the same time, fast charging causes the battery to age rapidly and reduces its performance.

Method used

A quick charge coating is applied to the overhang area of ​​the negative electrode sheet to cover the thinning area of ​​the first coating area to increase the lithium ion transmission channel and diffusion coefficient, slow down the accumulation of lithium in the fast charge layer, and improve the transportation speed of lithium ions.

Benefits of technology

It effectively reduces the lithium concentration enrichment in the overhang area, avoids lithium extraction, prevents the loss of active lithium, and improves the energy density, circulation performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852307A_ABST
    Figure CN119852307A_ABST
Patent Text Reader

Abstract

The invention discloses a negative pole piece, a preparation method thereof and a battery, the negative pole piece comprises a current collector, a first coating area and a second coating area, the first coating area is located in an area, opposite to a positive pole piece, of the negative pole piece; the second coating area is located in the overhang area of the negative pole piece, and the second coating area covers the thinning area of the first coating area; the coating material of the second coating area is a fast charging material, and the lithium ion diffusion coefficient of the second coating area is greater than that of the first coating area. The multiplying power characteristic of the second coating area is higher than that of the first coating area, a large contact area exists between the first coating area and the second coating area, lithium ions can be rapidly diffused to the active material layer from the overhang area in the discharging process and then return to the positive electrode, and removable active lithium is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode sheets, and in particular relates to a negative electrode sheet, a preparation method thereof and a battery. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] With the rapid growth of electric vehicles in recent years, along with the anxiety about battery life, new problems such as "difficult charging and slow charging" have become increasingly prominent. Since the overall energy density of lithium-ion batteries cannot be infinitely increased, the above problems can only be alleviated by increasing the charging speed, and the demand for fast-charging graphite negative electrode materials has also exploded.

[0004] Due to the SP2 hybridization of C atoms, graphite presents a layered structure, and lithium ions can only be embedded and extracted from the edges of the graphite layer, and cannot enter and exit from the direction perpendicular to the graphite layer. This is the fundamental reason that affects the fast charging of graphite. In addition, during fast charging, the electrochemical polarization increases. If lithium ions do not have time to diffuse into the graphite layers, they will be reduced to metallic lithium on the surface of the negative electrode. Its dendrite structure can easily pierce the diaphragm, causing an internal short circuit in the battery and leading to safety accidents; more importantly, during fast charging, due to the large current, the battery heats up rapidly, which may cause the temperature rise to fail to match the temperature threshold of the system, and may also cause rapid aging of the battery, resulting in reduced performance and increased safety risks.

[0005] During fast charging, the lithium ions corresponding to the overhang cannot be quickly removed and embedded in time, resulting in a continuous increase in the lithium concentration in the overhang area, which eventually leads to the production of lithium plating and loss of active lithium. The industry usually achieves this by drilling holes in the overhang of the pole piece or increasing the capacity of the overhang area. Among them, drilling holes in the overhang of the pole piece promotes the penetration of electrolyte in the overhang area and increases the transmission channel of lithium ions, which increases the transmission speed of lithium ions in the overhang area, and alleviates the reversible capacity loss caused by incomplete discharge to a certain extent; increasing the capacity of the overhang area, for example, using carbon materials with a larger discharge gram capacity in the edge area of ​​the current collector surface, increasing the surface capacity and interface state of the edge area, thereby improving edge lithium / sodium plating.

[0006] Although the use of high-capacity coatings can also improve the phenomenon of lithium deposition at the edges, it cannot completely solve the problem. When the lithium concentration exceeds the capacity of the coating, lithium deposition will also occur. The laser drilling method can only enhance the lithium ion transmission rate in the direction perpendicular to the electrode, and has little effect on the lithium ion transmission rate in other directions. Therefore, the improvement in the lithium ion transmission rate is limited and will cause irreversible damage to the material. Summary of the invention

[0007] In view of the deficiencies in the prior art, an object of the present invention is to provide a negative electrode plate, a preparation method thereof and a battery.

[0008] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0009] In a first aspect, the present invention provides a negative electrode plate, comprising a current collector, a first coating area and a second coating area, wherein the first coating area is located in an area opposite to the negative electrode plate and the positive electrode plate; the second coating area is located in an overhang area of ​​the negative electrode plate, and the second coating area covers a thinned area of ​​the first coating area;

[0010] The coating material of the second coating area is a fast-charging material, and the lithium ion diffusion coefficient of the second coating area is greater than the lithium ion diffusion coefficient of the first coating area.

[0011] In the design process of lithium-ion batteries, for safety reasons and to prevent lithium dissolution in the negative electrode, the area of ​​the negative electrode sheet is larger than that of the positive electrode sheet, that is, the edge of the negative electrode sheet extends beyond the positive electrode sheet by 1-3 mm. The area where the negative electrode sheet protrudes relative to the positive electrode sheet is called the "excess area" or "overhang area".

[0012] In order to improve the problem of lithium deposition in the overhang area, the inventors tried to coat a layer of fast-charging coating in the overhang area and coat a normal active material layer in the area opposite to the negative electrode plate to increase the transport speed of lithium ions and avoid lithium deposition caused by excessive lithium ion concentration at the edge of the negative electrode plate.

[0013] However, the inventors found that although this method can reduce lithium plating to a certain extent, there is an obvious interface between the fast-charging coating and the normal active material layer in the middle of the negative electrode plate, and the contact area is very small, resulting in a very small lithium ion transfer rate between the fast-charging coating and the active material layer in the overhang area. As the battery is charged and discharged, lithium ions continue to accumulate in the fast-charging coating, thereby reducing the concentration of lithium ions released from the negative electrode plate during the discharge process, which in turn has an adverse effect on the battery's energy density, cycle performance and safety.

[0014] The inventors also tried to set the thinning area of ​​the first coating area (i.e., the normal active material layer in the middle of the negative electrode plate) covered by the fast-charging coating (second coating area) in the overhang area, so that the contact area between the first coating area and the second coating area is effectively increased, that is, the lithium ion transport channel between the first coating area and the second coating area is effectively expanded, and the lithium ion diffusion coefficient of the second coating area is increased at the same time, so that the lithium ions embedded in the second coating area during charging can quickly diffuse to the first coating area during discharging, and de-embed through the first coating area and return to the positive electrode. The accumulation of lithium in the second coating area is effectively slowed down, and the concentration of active lithium that can be removed is effectively increased. It has a relatively good promoting effect on the energy density, cycle performance and safety of the battery.

[0015] In some embodiments, the relationship between the lithium ion diffusion coefficient D1 of the first coating region and the lithium ion diffusion coefficient D2 of the second coating region is: D2 = (1.1-100) D1.

[0016] In some embodiments, the coverage width between the second coating area and the first coating area is 0.5-2 mm.

[0017] In some embodiments, the thickness of the second coated region is 15-50 μm less than the thickness of the first coated region.

[0018] Preferably, the porosity of the second coating region is greater than the porosity of the first coating region.

[0019] Preferably, the coating width of the second coating zone is 0.5-5 mm.

[0020] In some embodiments, the material of the second coating region is at least one selected from graphite, silicon carbon, soft carbon, lithium titanate, mesophase carbon microbeads, or hard carbon.

[0021] For example, the fast charging material can be graphite-hard carbon-mesophase carbon microspheres, hard carbon-mesophase carbon microspheres-lithium titanate, etc.

[0022] In a second aspect, the present invention provides a method for preparing the negative electrode sheet, comprising the following steps:

[0023] Apply slurry 1 to the middle of the current collector and the area opposite to the positive electrode sheet, and obtain a first coating area after drying;

[0024] The slurry 2 is applied to the overhang area of ​​the current collector and covers the thinned area of ​​the first coating area, and after drying, the second coating area is obtained.

[0025] Alternatively, the first coating area and the second coating area are dried together after coating.

[0026] In some embodiments, the pressure during coating at the second coating zone is less than the pressure during coating at the first coating zone.

[0027] In a third aspect, the present invention provides a battery, whose negative electrode plate is the negative electrode plate described above.

[0028] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0029] Applying a fast-charging coating (second coating area) to the overhang area can effectively reduce lithium concentration enrichment in the overhang area, avoid lithium precipitation in this area, and prevent the loss of active lithium;

[0030] The rate characteristic of the fast charging layer is higher than that of the active material layer (first coating area), and the contact area between the first coating area and the second coating area is larger. There are more lithium ion transport channels between the two coating areas. During the discharge process, lithium ions can quickly diffuse from the overhang area to the active material layer, and then return to the positive electrode, increasing the amount of active lithium that can be removed. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0032] Figure 1 This is a schematic diagram of the electrode plane. 1: first coating area; 2: second coating area, 3: blank area;

[0033] Figure 2 Cycle comparison diagram of different embodiments and comparative examples. DETAILED DESCRIPTION

[0034] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0035] The present invention will be further described below in conjunction with the embodiments.

[0036] Generally, there will be a space in the middle of the coating area for the foil to be die-cut into the tabs. This uncoated area is called the blank area.

[0037] Example 1

[0038] Graphite, carboxymethyl cellulose CMC, styrene-butadiene rubber SBR and spandex SP are pulped in a ratio of 96:1:2:1, with a viscosity of 5000 and a solid content of 50%, to obtain slurry 1;

[0039] Hard carbon, CMC, SBR and SP were slurried in a ratio of 96:1:2:1, with a viscosity of 5000 and a solid content of 50%, to obtain slurry 2;

[0040] Slurry 1 and slurry 2 are applied to the copper foil by extrusion coating. Slurry 1 is applied to the middle area of ​​the copper foil opposite to the positive electrode plate to obtain the first coating area. Slurry 2 is applied to the overhang area with a coating width of 2 mm. The width of the thinned area covered by slurry 1 is 1.5 mm to obtain the second coating area. After the electrode sheet is dried, the negative electrode sheet is obtained, and the negative electrode sheet is processed into sheets and the battery is assembled.

[0041] Copper foil thickness: 6μm, width 230μm, slurry 1 coating density 80g / m 2 .

[0042] In the prepared negative electrode sheet, the thickness of the first coating area is 160 μm, and the lithium ion diffusion coefficient is 2.0×10 -11 cm 2 -s -1 The second coating area has a width of 2 mm, a thickness of 140 μm, and a lithium ion diffusion coefficient of 2.3×10 -10 cm 2 -s -1 , the overlapping width is 1.5mm.

[0043] Example 2

[0044] Graphite, CMC, SBR and SP were slurried in a ratio of 96:1:2:1, with a viscosity of 3000 and a solid content of 48%, to obtain slurry 1;

[0045] Soft carbon, CMC, SBR and SP were slurried in a ratio of 96:1:2:1, with a viscosity of 3000 and a solid content of 48%, to obtain slurry 2;

[0046] Slurries 1 and 2 are applied to the copper foil by extrusion coating. Slurry 1 is applied to the middle area of ​​the copper foil opposite to the positive electrode plate to obtain the first coating area. Slurry 2 is applied to the overhang area. Slurry 2 covers the thinned area of ​​slurry 1 to obtain the second coating area. After the electrode sheet is dried, the negative electrode sheet is obtained, and the sheet making and battery assembly are carried out.

[0047] In the prepared negative electrode sheet, the first coating area is the same as that in Example 1, the second coating area has a width of 2 mm, a thickness of 130 μm, and a lithium ion diffusion coefficient of 4.7×10 -11 cm 2 -s -1 , the overlapping width is 1.5mm.

[0048] Example 3

[0049] Graphite, CMC, SBR and SP were slurried in a ratio of 96:1:2:1, with a viscosity of 7000 and a solid content of 55%, to obtain slurry 1;

[0050] Lithium titanate, CMC, SBR and SP were slurried in a ratio of 96:1:2:1, with a viscosity of 7000 and a solid content of 55%, to obtain slurry 2;

[0051] Slurries 1 and 2 are applied to the copper foil by extrusion coating. Slurry 1 is applied to the middle area of ​​the copper foil opposite to the positive electrode plate to obtain the first coating area. Slurry 2 is applied to the overhang area. Slurry 2 covers the thinned area of ​​slurry 1 to obtain the second coating area. After the electrode sheet is dried, sheet making and battery assembly are carried out.

[0052] In the prepared negative electrode sheet, the first coating area is the same as that in Example 1, the thickness of the second coating area is 140 μm, and the lithium ion diffusion coefficient is 1.6×10 -10 cm 2 -s -1 , the overlapping width is 1.5mm.

[0053] Comparative Example 1

[0054] The difference from Example 1 is that only slurry 1 is used for coating.

[0055] Graphite, CMC, SBR and SP were slurried in a ratio of 96:1:2:1, with a viscosity of 5000 and a solid content of 50%, to obtain slurry 1;

[0056] The slurry 1 is applied to the copper foil by extrusion coating. The coating process is the same as that in Example 1. After the electrode is dried, the electrode is prepared and the battery is assembled.

[0057] Comparative Example 2

[0058] The difference from Example 1 is that only the compositions of slurry 1 and slurry 2 are interchanged, and the rest are the same as Example 1.

[0059] Hard carbon, CMC, SBR and SP were slurried in a ratio of 96:1:2:1, with a viscosity of 5000 and a solid content of 50%, to obtain slurry 1;

[0060] Graphite, CMC, SBR, and SP were slurried in a ratio of 96:1:2:1, with a viscosity of 5000 and a solid content of 50%, to obtain slurry 2;

[0061] Apply slurries 1 and 2 to the copper foil by extrusion coating. Apply slurry 1 to the middle area of ​​the copper foil opposite to the positive electrode plate, and apply slurry 2 to the overhang area. Slurry 2 covers the thinned area of ​​slurry 1. After the electrode sheet is dried, sheet making and battery assembly are carried out.

[0062] Comparative Example 3

[0063] The difference from Example 1 is that slurry 1 and slurry 2 are coated in parallel, and there is no overlapping area between the two coating layers. The rest is the same as Example 1.

[0064] Preparation of soft-pack lithium-ion batteries: The negative electrode sheets prepared in Examples 1-3 and Comparative Examples 1-3 were combined with commercial lithium iron phosphate positive electrodes, the electrolyte was 1 mol / LLiPF6 / EC+PC+DEC+EMC (volume ratio 1:0.3:1:1), the diaphragm was a PP / PE / PP three-layer diaphragm with a thickness of 14 μm, and a soft-pack battery of about 27 Ah was made. The full battery performance test was carried out in the range of 2.5V-3.65V, and the battery cells were fully discharged and disassembled at 100, 200, 500, and 1000cls per cycle. The powder in the second electrode area was scraped for ICP testing to detect changes in lithium concentration.

[0065] Table 1

[0066]

[0067]

[0068] Figure 2 It is a cycle comparison diagram of Example 1-3 and Comparative Example 1-2. Figure 2 It can be seen that Example 1 has the best cycle performance, and coating the edge with a material with a large lithium ion diffusion coefficient has a certain improvement in the cycle performance, and the better the fast charging performance of the material, the more obvious the cycle improvement.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A negative electrode plate, characterized in that: It includes a current collector, a first coating area and a second coating area, wherein the first coating area is located in the area opposite to the negative electrode sheet and the positive electrode sheet; the second coating area is located in the overhang area of ​​the negative electrode sheet, and the second coating area covers the thinned area of ​​the first coating area; The coating material of the second coating area is a fast-charging material, and the lithium ion diffusion coefficient of the second coating area is greater than the lithium ion diffusion coefficient of the first coating area.

2. The negative electrode sheet according to claim 1, characterized in that: The relationship between the lithium ion diffusion coefficient D1 of the first coating area and the lithium ion diffusion coefficient D2 of the second coating area is: D2 = (1.1-100) D1.

3. The negative electrode sheet according to claim 1, characterized in that: The coverage width between the second coating area and the first coating area is 0.5-2 mm.

4. The negative electrode sheet according to claim 3, characterized in that: The thickness of the second coating area is 15-50 μm smaller than the thickness of the first coating area.

5. The negative electrode sheet according to claim 4, characterized in that: The porosity of the second coated region is greater than the porosity of the first coated region.

6. The negative electrode plate according to claim 1, characterized in that: The coating width of the second coating area is 0.5-5 mm.

7. The negative electrode plate according to claim 1, characterized in that: The material of the second coating area is at least one selected from graphite, silicon carbon, soft carbon, lithium titanate, mesophase carbon microbeads or hard carbon.

8. The method for preparing the negative electrode sheet according to any one of claims 1 to 7, characterized in that: The steps include: Apply slurry 1 to the middle of the current collector and the area opposite to the positive electrode sheet, and obtain a first coating area after drying; The slurry 2 is applied to the overhang area of ​​the current collector and covers the thinned area of ​​the first coating area, and after drying, the second coating area is obtained. Alternatively, the first coating area and the second coating area are dried together after coating.

9. The method for preparing the negative electrode sheet according to claim 8, characterized in that: The pressure during coating in the second coating zone is lower than the pressure during coating in the first coating zone.

10. A battery, characterized in that: The negative electrode plate is the negative electrode plate described in any one of claims 1-7.

Citation Information

Patent Citations

  • Negative plate, battery and preparation method of negative plate

    CN113097428A

  • Negative plate and battery comprising same

    CN114597335A

  • Negative plate and application thereof

    CN115295753A

  • Negative pole piece and secondary battery comprising same

    CN115810718A

  • Negative pole piece and preparation method thereof, battery and power utilization device

    CN117293274A